Social (media) vigilantes: effects of social vigilantism and anonymity on online confrontations of prejudice - Lawless, Tiffany Jo (Kansas State University, 2023)
Research has focused on how anonymity affects perceptions of prejudice online (e.g., Lawless & Saucier, submitted a), but it is possible individual differences like Social Vigilantism (SV), the tendency to impress one’s beliefs onto others, also affect these perceptions (Saucier & Webster, 2010). In Study 1, SV is measured and participants see mock prejudiced posts in a within-groups 2(anonymous/identifiable) x 2(including/not including comments confronting posts) design and rate perceptions of posts (e.g., The person who posted this is racist). Study 2 uses the same methods as Study 1 but asks participants how they would interact with posts. It is shown that SV is associated with more confrontation of prejudice because SV is associated with counterarguing. It is also demonstrated that anonymity of platform affects the results such that posts on identifiable platforms receive more interactions because they are seen as more honest.
Keywords: Social media; Prejudice; Racism; Internet; Social vigilantism; Confrontation